Corporations need to look beyond profits - Lisa Sachs; Jeffrey Sachs; Nathan Lobel (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2017)
Lilac Nachum's Columbia FDI Perspective argues that society is best served when companies focus on maximizing profits rather than on their social and environmental impacts. This follows the logic of an idealized free-market economy. In practice, we argue, companies should take responsibility for the impacts they have on other stakeholders.
Keywords: 330